Comparison of Influence of the Fast Atom Beam and Ion Beam on the Metal Target - Pushkarev A. I. Aleksandr Ivanovich; Prima A. I. Artem Igorevich; Myshkin (Mishkin) V. F. Vyacheslav Fedorovich; Chistyakova N. V. Nadezhda Vladimirovna; Ezhov V. V. Vitali Vladimirovich (2021, 2021)
Title screen